Regulation of continuous but complex expression pattern of Six1 during early sensory development. Issue 1 (30th November 2017) - Sato, Shigeru; Furuta, Yasuhide; Kawakami, Kiyoshi
Abstract : Background : In vertebrates, cranial sensory placodes give rise to neurosensory and endocrine structures, such as the olfactory epithelium, inner ear, and anterior pituitary. We report here the establishment of a transgenic mouse line that expresses Cre recombinase under the control of Six1‐21, a major placodal enhancer of the homeobox gene Six1 .Results : In the new Cre‐expressing line, mSix1‐21‐NLSCre, the earliest Cre‐mediated recombination was induced at embryonic day 8.5 in the region overlapping with the otic‐epibranchial progenitor domain (OEPD), a transient, common precursor domain for the otic and epibranchial placodes. Recombination was later observed in the OEPD‐derived structures (the entire inner ear and the VIIth–Xth cranial sensory ganglia), olfactory epithelium, anterior pituitary, pharyngeal ectoderm and pouches. Other Six1 ‐positive structures, such as salivary/lacrimal glands and limb buds, were also positive for recombination. Moreover, comparison with another mouse line expressing Cre under the control of the sensory neuron enhancer, Six1‐8, indicated that the continuous and complex expression pattern of Six1 during sensory organ formation is pieced together by separate enhancers.Conclusions : mSix1‐21‐NLSCre has several unique characteristics to make it suitable for analysis of cell lineage and gene function in sensory placodes as well as nonplacodal Six1 ‐positive structures. Developmental Dynamics 247:250–261, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: The new Cre‐expressing mouse line (Six1‐21‐NLSCre) was established. The Cre line induced genetic recombination in the progenitor domain for otic/epibranchial placodes, olfactory epithelium and Rathke's pouch. The recombination pattern was similar yet distinct from Pax2‐Cre/Pax8‐Cre lines. The results suggested that the continuous but complex expression pattern of Six1 during sensory organ formation is pieced together by separate enhancers. The Cre line should be useful to understand sensory development.